Beta-Blocker Use in Patients Undergoing Non-Cardiac Surgery: A Systematic Review and Meta-Analysis - Doménica Herrera Hernández; Bárbara Abreu; Tania Siu Xiao; Andreina Rojas; Kevin López Romero; Valentina Contreras; Sol Villa Nogueyra; Zulma Sosa; Samantha M. Alvarez; Camila Sánchez Cruz; Ernesto Calderón Martinez (Medical Sciences)
Background: The use of beta-blockers in the perioperative period has been widely investigated due to their potential to reduce the risk of major adverse cardiovascular and cerebrovascular events (MACCE) and mortality; yet their overall impact on various postoperative outcomes remains debated. This study constitutes a systematic review and meta-analysis of the impact of beta-blockers on mortality, MI, stroke, and other adverse effects such as hypotension and bradycardia in patients undergoing non-cardiac surgery. Methods: A comprehensive systematic review and meta-analysis were conducted according to PRISMA 2020 guidelines. Searches were performed across PubMed, Cochrane, Web of Science, Scopus, EMBASE, and CINAHL databases; we included randomized controlled trials and cohort and case-control studies published from 1999 to 2024. Results: This meta-analysis included data from 28 studies encompassing 1,342,430 patients. Perioperative beta-blockers were associated with a significant increase in stroke risk (RR 1.42, 95% CI: 1.03 to 1.97, p = 0.03, I2 = 62%). However, no statistically significant association was found between beta-blocker use and mortality (RR 0.62, 95% CI: 0.38 to 1.01, p = 0.05, I2 = 100%). Subgroup analyses revealed a protective effect on mortality for patients with high risks, such as patients with a history of atrial fibrillation, chronic heart failure, and other arrhythmias. For myocardial infarction (RR 0.82, 95% CI: 0.53 to 1.28, p = 0.36, I2 = 86%), a reduction in events was observed in the subgroup of randomized controlled trials. Beta-blockers significantly increased the risk of hypotension (RR 1.46, 95% CI: 1.26 to 1.70, p < 0.01, I2 = 25%) and bradycardia (RR 2.26, 95% CI: 1.37 to 3.74, p < 0.01, I2 = 64%). Conclusions: Perioperative beta-blockers show increasing rates of stroke events following non-cardiac surgery but do not significantly impact the incidence of MI or mortality. The increased risks of hypotension and bradycardia necessitate careful patient selection and monitoring. Future research should aim to refine patient selection criteria and optimize perioperative management to balance the benefits and risks of beta-blocker use in surgical settings.